Analisis Personal Higiene Penjagal dan Sanitasi Pengelolaan Limbah Di UPTD Rumah Pemotongan Hewan (RPH) Kota Depok - Fanny Rizky Ramadhani; Ony Linda; Rismawati Pangestika (Fakultas Kesehatan Masyarakat Universitas Andalas, 2022)
Slaughterhouse is one of the facilities that can produce meat products with safe, healthy, whole and halal quality but there are still many things that must be considered related to slaughterer hygiene and waste management sanitation because slaughterhouse activities produce waste and are closely related to cross contamination . The purpose of this study was to determine the personal hygiene of butchers and sanitation of waste management in slaughterhouses. This research was conducted at the Depok City Slaughterhouse with descriptive qualitative type. Data were obtained from 7 informants consisting of 3 animal butchers and 2 Sanitation and Waste Management Coordination Staff as main informants, 1 head of UPTD RPH as key informants and 1 cleaning officer as supporting informant using structured interview guidelines, observation and document review conducted on March-December 2021. Data analysis includes data reduction, data presentation and decision making. The results of the study found that the variables that met the requirements of Minister of Agriculture No. 13 of 2010 and SNI 01-6159- 1999 were Slaughterhouses (is this a variable? The dependent variable, ma'am), Availability of Trash Cans, Availability of SPAL, Sanitation of Slaughterhouses, Waste Management Behavior. does not meet the requirements, namely Health of Butchers or Workers, Personal Protective Equipment, Handwashing Behavior. The researcher's advice for the abattoir is to always supervise and provide and complete the facilities needed by butchers and workers. Keywords: Butcher, Slaughterhouse